Transformation of the social status of the mother: problems and solutions - Abdirashid Mamasidikovich Mirzakhmedov; Sevara Akramovna Pardaeva (Genius Journals, 2022)
This article is devoted to the analysis of the social analysis of the status of the mother in the conditions of modern society, which is subject to modernization under the pressure of socio-economic progress of the world. A comparative approach is carried out to study the traditional and liberal, universal and national culture of the mother as a family value. The purpose of the article is socio-psychological analysis of the socio-psychological characteristics of the status of women in family life. Research methods of this article appeared "Pedagogical Poems" by A. S. Makarenko, the philosophy of education of J. Dewey, as well as sociological observations and surveys conducted in 2021 in the regions of the Fergana Valley of Uzbekistan and partially kyrgyzstan
Keywords: Family and mother; child; marriage and family; family stability